2013
DOI: 10.1007/s00429-013-0508-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of parvalbumin and calretinin interneurons in the prefrontal cortex during adolescence

Abstract: Determining the normal developmental trajectory of individual GABAergic components in the prefrontal cortex (PFC) during the adolescent transition period is critical because local GABAergic interneurons are thought to play an important role in the functional maturation of cognitive control that occurs in this developmental window. Based on the expression of calcium-binding proteins, 3 distinctive subtypes of interneurons have been identified in the PFC: parvalbumin (PV)-, calretinin (CR)-, and calbindin (CB)-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
158
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(176 citation statements)
references
References 58 publications
18
158
0
Order By: Relevance
“…This pattern of HPC septotemporal PV gradient was selective to CA1 and DG regions, with CA3 regions showing a more consistent pattern of PV expression across the long axis in all age groups. Thus, our data support a growing body of evidence describing age-related variation in the expression of PV across the rat life span [[48], [58,59,60]; for a review, see [49]]. Such findings are also consistent with studies reporting age-related decreases in PV expression within the HPC [61,62,63,64].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This pattern of HPC septotemporal PV gradient was selective to CA1 and DG regions, with CA3 regions showing a more consistent pattern of PV expression across the long axis in all age groups. Thus, our data support a growing body of evidence describing age-related variation in the expression of PV across the rat life span [[48], [58,59,60]; for a review, see [49]]. Such findings are also consistent with studies reporting age-related decreases in PV expression within the HPC [61,62,63,64].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, PV likely varies within that multimonth window across the three main HPC subregions, and likely exhibits variation within these across the septotemporal axis. Evidence of this dynamic expression has been shown by Caballero et al [59], reporting that ventral HPC subregions exhibit increases in PV+ neurons up to P65-75 (roughly 2 months of age) in a pattern similar to prefrontal cortical areas [59,60]. With the exception of the cingulate cortex, the present work provides evidence for the stable expression of PV regardless of age within many neocortical areas (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Studies in non-human primates and rodents have revealed that normal PFC development involves significant increases in GABAergic function, including an increase in the expression and excitability of fast-spiking, parvalbumin-positive GABAergic interneurons (Caballero et al, 2014), an increase in spontaneous inhibitory postsynaptic currents in the pyramidal cells on which these interneurons synapse (Hashimoto et al, 2009;Cass et al, 2014), and changes in the subunit composition of GABAA receptors that would facilitate inhibitory transmission (Datta et al, 2015). In addition, dopaminergic control of inhibitory signaling in the PFC changes significantly during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, adolescent maturation of gamma-amino butyric acid (GABA)-secreting interneurons of the PFC has also been reported (Caballero et al 2014). A recent longitudinal magnetic resonance imaging (MRI) study in rats has also identified a peak in cortical thickness during adolescence and a continued increase in volume of cerebral cortex and striatum and myelination from adolescence to adulthood (until PND60) (Mengler et al 2014).…”
Section: Figure 1-1 Adolescence In Rodents and Neural Maturation Chanmentioning
confidence: 97%